PROGRAM GERAKAN LITERASI SEKOLAH (GLS) DI MTS MAFATIHUL HUDA DEPOK - siti maesaroh; Beby Banowati; Ahmaf Faozan; Nuniek Rahmatika (UI Cirebon (Universitas Islam Cirebon), 2022)
ABSTRACKKnowledge and insight can be obtained with a shortcut, namely reading. Reading is the first thing in literacy activities. Reading requires deep understanding or nothing else than reasoning. The higher a person's reasoning in reading, of course, the more understanding he will understand what he reads. To achieve this is not easy, it needs habituation and continuity, especially for students who should as knowledge takers certainly do not escape reading activities. From there, the author tries to question and implement one of the programs launched by the Ministry of Education in 2015 namely the School Literacy Movement (GLS) at MTs Mafatihul Huda. However, the implementation of the program was slightly modified. The modification lies in the time of reading books, and the application of the six basic literacy. This research is intended as an effort to minimize the low reading interest of students at the first level, especially at MTs Mafatihul Huda. With a qualitative research method with a case study approach. And using three qualitative data analysis activities, namely data reduction, data modeling and drawing conclusions. So the results of the study indicate that students' reading interest is still low due to the minimal availability of reading materials, the available books are still old editions, the existence of reading corners that are not well maintained, librarians who hold concurrent positions, and the literacy culture in madrasas has not been maximally developed.